Challenges and Solutions of Risk Management in Software Ecosystems - Campos, Gabriele da Silva Serafim de; Silva, Francisco Ismael Ribeiro da; Malcher, Paulo; Santos, Rodrigo Pereira dos (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2026: Anais do XXII Simpósio Brasileiro de Sistemas de InformaçãoDO - 10.5753/sbsi.2026.248578, 2026)
Research Context: Software ecosystems (SECO) differ from other software development contexts and increase the complexity of risk management. Scientific and/or Practical Problem: It remains unclear the way risk management is conducted in SECO, which risks are specific to this context, and which solutions have been proposed. Proposed Analysis: This study investigates risk management in SECO by identifying SECO-specific risks, mapping solutions and their evaluations, and highlighting existing challenges. Related IS Theory. Socio-technical Theory provides a perspective by emphasizing the interdependence of technical and social factors in risk management in SECO. Research Method: We conducted a systematic mapping study following established guidelines, including study selection, data extraction, and qualitative coding. Summary of Results: We identified 24 SECO-specific risks, 21 solutions, of which 15 were evaluated, and 14 challenges related to risk management in SECO. Contributions and Impact to IS area: This study consolidates knowledge on risk management in SECO and provides insights to support researchers and practitioners in designing more effective mitigation strategies.